Effect of vitamin D supplementation on non-skeletal disorders: a systematic review of meta-analyses and randomised trials. Issue 12 (December 2017) - Autier, Philippe; Mullie, Patrick; Macacu, Alina; Dragomir, Miruna; Boniol, Magali; Coppens, Kim; Pizot, Cécile; Boniol, Mathieu
Summary: Randomised trials reported up to Dec 31, 2012, did not confirm that vitamin D supplementation could protect from non-skeletal health conditions affecting adults, as was expected on the basis of data from observational studies. To examine whether the more recently published meta-analyses and trials would change past conclusions, we systematically reviewed meta-analyses of vitamin D supplementation and non-skeletal disorders published between Jan 1, 2013, and May 31, 2017, that included study participants of all ages, including pregnant women. We also searched for randomised trials not included in meta-analyses. We identified 87 meta-analyses, of which 52 were excluded because they contained less recent literature or were of suboptimal quality. We retrieved 202 articles on trials that were not included in meta-analyses. Recent meta-analyses reinforce the finding that 10–20 μg per day of vitamin D can reduce all-cause mortality and cancer mortality in middle-aged and older people. Although vitamin D doses were greater than those assessed in the past, we found no new evidence that supplementation could have an effect on most non-skeletal conditions, including cardiovascular disease, adiposity, glucose metabolism, mood disorders, muscular function, tuberculosis, and colorectal adenomas, or on maternal and perinatal conditions. New data on cancer outcomes were scarce. The compilation of results from 83 trials showed that vitamin D supplementation had no significant effect on biomarkers of systemic inflammation. The main new finding highlighted by this systematic review is that vitamin D supplementation might help to prevent common upper respiratory tract infections and asthma exacerbations. There remains little evidence to suggest that vitamin D supplementation has an effect on most conditions, including chronic inflammation, despite use of increased doses of vitamin D, strengthening the hypothesis that low vitamin D status is a consequence of ill health, rather than its cause. We further hypothesise that vitamin D supplementation could exert immunomodulatory effects that strengthen resistance to acute infections, which would reduce the risk of death in debilitated individuals. We identified many meta-analyses of suboptimal quality, which is of concern. Future systematic reviews on vitamin D should be based on data sharing so that data for participants with the same outcomes measured in the same way can be pooled to generate stronger evidence.